Dependence on the thermodynamic state of self-diffusion of pseudo-hard-sphere and Lennard-Jones potentials - Marchioni, Leandro (2023)
Self-diffusion D in a system of particles that interact with a pseudo-hard-sphere or a Lennard-Jones potential is analyzed. Coupling with a solvent is represented by a Langevin thermostat, characterized by the damping time td. The hypotheses that D=D0φ is proposed, where D0 is the small concentration diffusivity and φ is a thermodynamic function that represents the effects of interactions as concentration is increased. Molecular dynamics simulations show that different values of the noise intensity modify D0, but do not have an effect on φ. This result is consistent with the assumption that φ is a thermodynamic function since the thermodynamic state is not altered by the presence of damping and noise.